2015
DOI: 10.1099/jgv.0.000276
|View full text |Cite
|
Sign up to set email alerts
|

NK-cells are involved in thymic atrophy induced by influenza A virus infection

Abstract: NK-cells have traditionally been viewed as innate effector lymphocytes that serve as a first line of defence against a range of viruses and tumours. More recently, the importance of NK-cell immunoregulatory functions has been highlighted. NK-cells can inhibit antiviral T-cell responses, and also play an important role in controlling harmful T-cell activity in autoimmunity and transplantation settings. Moreover, immunopathological effects of NK-cells during infection have been reported. Nevertheless, the phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Because conducting research investigations on the thymuses of HIV-infected humans (Verinaud et al 2004) is difficult, many animal model systems have been developed. The simian immunodeficiency virus (SIV)-infected monkey model is much better than the feline and murine models, on the basis that this species not only acts as a natural host for the infection, but also offers Duan et al 2015;Hu et al 2016;Liu et al 2014 Parasites…”
Section: Pathogenic Infections and Ati Viral Infections And Atimentioning
confidence: 99%
See 3 more Smart Citations
“…Because conducting research investigations on the thymuses of HIV-infected humans (Verinaud et al 2004) is difficult, many animal model systems have been developed. The simian immunodeficiency virus (SIV)-infected monkey model is much better than the feline and murine models, on the basis that this species not only acts as a natural host for the infection, but also offers Duan et al 2015;Hu et al 2016;Liu et al 2014 Parasites…”
Section: Pathogenic Infections and Ati Viral Infections And Atimentioning
confidence: 99%
“…This investigation explored the phenotype and immunological functions of natural killer (NK) cells and demonstrated that production of interferon (IFN)-γ by the NK cells caused the involution of thymus during the course of an IAV infection (Duan et al 2015). Similarly, influenza A virus type H1N1pmd09 infection induced severe ATI and depletion of the DP cells as a result of apoptosis.…”
Section: Paracoccidioides Brasiliensismentioning
confidence: 99%
See 2 more Smart Citations
“…The mouse-adapted influenza A/Puerto Rico/8/34 (H1N1; PR8) virus was propagated as described previously (Duan et al, 2015;Zhou et al, 2016). 100 IU/ml penicillin, and 100 μg/ml streptomycin (Invitrogen).…”
Section: Virus and Plaque Assaymentioning
confidence: 99%